2011
DOI: 10.1108/14757701111129616
|View full text |Cite
|
Sign up to set email alerts
|

Apparent audit failures and value relevance of earnings and book value

Abstract: Purpose-The purpose of this paper is to examine the value relevance of accounting information in cases of apparent audit failures. Design/methodology/approach-The authors adopt the bootstrapping technique and compare the value relevance of key accounting information across samples of firms experiencing apparent audit failures with matched non-audit failure firms. Findings-Accounting information is found to be less value relevant for firms experiencing apparent audit failures, regardless of auditor reputation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
7
0
5
Order By: Relevance
“…A detail audit work is necessary to avoid audit failures. Dang et al (2011) reported that firms with audit failures experiencing lesser value relevance. Ittonen and Peni (2012) documented that female auditors provides high-quality and efficient audit work.…”
Section: Audit Partner Gender and Value Relevancementioning
confidence: 99%
“…A detail audit work is necessary to avoid audit failures. Dang et al (2011) reported that firms with audit failures experiencing lesser value relevance. Ittonen and Peni (2012) documented that female auditors provides high-quality and efficient audit work.…”
Section: Audit Partner Gender and Value Relevancementioning
confidence: 99%
“…Also, studies have analyzed firm characteristics that affect investors' valuation of earnings and book value of equity. For instance, the value relevance of financial statements has been shown to be contingent on a firm's profitability and financial health (Barth, Beaver, & Landsman, 1998;Basu, 1997;Collins et al, 1999;Elliott & Hanna, 1996;Hayn, 1995), investment in intangibles (Collins et al, 1997;Srivastava, 2014), internal and external monitoring mechanisms (Dang, Brown, & McCullough, 2011;Marquardt & Wiedman, 2004), and information environment (Bartov, Goldberg, & Kim, 2005). Barth, Li, and McClure (2018) analyzed the evolution of value relevance of accounting information from 1962 to 2014 and found a considerable increase in the value relevance of intangible assets, growth opportunities, and alternative performance measures, which are important in the new economy.…”
Section: Comparability and The Value Relevance Of Accounting Informmentioning
confidence: 99%
“…Also, studies have analyzed firm characteristics that affect investors' valuation of earnings and book value of equity. For instance, the value relevance of financial statements has been shown to be contingent on a firm's profitability and financial health (Barth, Beaver, & Landsman, 1998; Basu, 1997; Collins et al, 1999; Elliott & Hanna, 1996; Hayn, 1995), investment in intangibles (Collins et al, 1997; Srivastava, 2014), internal and external monitoring mechanisms (Dang, Brown, & McCullough, 2011; Marquardt & Wiedman, 2004), and information environment (Bartov, Goldberg, & Kim, 2005).…”
Section: Prior Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Entretanto, a despeito de a reputação ser um atributo relevante para as empresas auditadas, os incentivos a tal preferência devem ser contextualizados, pois, isoladamente, eles podem não se materializar. Dang, Brown & McCullough (2011) verificaram que a reputação do auditor é um aspecto valorizado para sua contratação, já que reforça a reputação da empresa auditada; porém, em termos de Value Relevance, quando a empresa auditada se envolve em casos de fraudes ou erros, a qualidade da informação contábil reduz independentemente de a empresa ser auditada por uma Big4 ou Não Big4. Isso indica que, em condições normais, ser auditado por uma BigN, tende a gerar um prêmio pela reputação do auditor, o que não acontecerá quando a empresa auditada se envolver em alguma irregularidade (erro ou fraude).…”
Section: Reputação Do Auditor E Concentração Do Mercado De Auditoriaunclassified
“…Peytcheva & Gillet (2012) observam que a qualidade do serviço de auditoria é uma função da sua reputação; entretanto, essa reputação sofre efeito de outros fatores, tais como o envolvimento prévio do auditor em casos anteriores de fraude e erro, o que corrobora o apresentado por Dang, Brown & McCullough (2011). Ou seja, a qualidade do auditor sofre efeito de diversos fatores, entre eles a reputação do auditor.…”
Section: Reputação Do Auditor E Concentração Do Mercado De Auditoriaunclassified